Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/10495398.2013.836530
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiling of Glucose Transporter 1 (GLUT1) and Apoptotic Genes (BAX and BCL2) in Milk Enriched Mammary Epithelial Cells (MEC) in Riverine Buffalo during Lactation

Abstract: Lactation is an important physiological process in dairy animals. During lactation, up to 85% of the body glucose is directed toward the mammary glands for milk synthesis. Studies related to lactation physiology are generally carried out on mammary biopsies, which may adversely affect animal health. In the present study, milk enriched MEC were used to study the expression pattern of GLUT1 and apoptotic genes (BAX and BCL2) across different stages of lactation in riverine buffalo in relation to milk yield. MEC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…[24] could explain the relatively low levels of CSN2 , CSN3 , CSN1S1 and CSN2S2 when compared with our data, suggesting that the antibody-captured milk MEC technique used by these authors was probably not optimal. The validity of gene expression results obtained by using purified MEC has been demonstrated in cows and buffalo [31, 3336] and supported by our data. The advantages of purified MEC as a non-invasive source of RNA for mammary gland transcriptome analysis include but not limited to possibility for repeat sampling over a period of time on the same animals without causing damage to mammary tissue and ability to specifically study milk secreting cells.…”
Section: Discussionsupporting
confidence: 87%
“…[24] could explain the relatively low levels of CSN2 , CSN3 , CSN1S1 and CSN2S2 when compared with our data, suggesting that the antibody-captured milk MEC technique used by these authors was probably not optimal. The validity of gene expression results obtained by using purified MEC has been demonstrated in cows and buffalo [31, 3336] and supported by our data. The advantages of purified MEC as a non-invasive source of RNA for mammary gland transcriptome analysis include but not limited to possibility for repeat sampling over a period of time on the same animals without causing damage to mammary tissue and ability to specifically study milk secreting cells.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the effect of Quinagolide, a prolactin-release inhibitor, was similar regardless of the anti-cytokeratin antibody used: anti-cytokeratin 8 ( Boutinaud et al, 2012 ) or anti-cytokeratin 1, 5, 10, and 14 ( Lollivier et al, 2015 ). In addition, the effect of the lactation stage was concordant in two bovine studies ( Sigl et al, 2012 ; Boutinaud et al, 2013b ) as well as one bovine study and one buffalo study ( Boutinaud et al, 2013b ; Yadav et al, 2014 ) where different antibodies were used ( Table 1 ). Finally, the agreement of these different studies suggests that the immunomagnetic method of MEC purification is reliable.…”
Section: The Methodology For Using Mec From Milk To Analyze Mammary Gmentioning
confidence: 79%
“…Goat milk contains a higher concentration of MEC than bovine milk ( Boutinaud and Jammes, 2002 ). Thus, 1.8–3.6 kg of bovine milk ( Boutinaud et al, 2008 , 2012 , 2014 ; Krappmann et al, 2012 ; Sigl et al, 2014 ), 0.9–1.6 kg of caprine milk ( Ben Chedly et al, 2011 , 2013 ) and 1 kg of buffalo milk ( Yadav et al, 2014 ) were used to extract purified MEC from milk in order to analyze mammary transcripts. During the second step of MEC isolation, an immunomagnetic separation technique is used to isolate the MEC from the total milk somatic cells and to remove the leukocytes.…”
Section: The Methodology For Using Mec From Milk To Analyze Mammary Gmentioning
confidence: 99%
See 1 more Smart Citation
“…So the Bcl-2/Bax ratio is important to MM cell fate after chemotherapy. However, it has been reported that downregulation of Homer1b/c using specific siRNA protects neurons against neurotoxicity-induced apoptosis through an increase in Bcl-2 with a decrease in Bax (14,35,36). Thus, we suspected that, after chemotherapy, increased expression of Homer1b/c might promote cell apoptosis through the classical mitochondrial apoptotic pathway.…”
Section: Discussionmentioning
confidence: 93%